A Guide to the NHS. - White, Tony (CRC Press, 2016)
To maximise the effectiveness of their work, NHS employees need a clear understanding of the structures and systems of the organisation in which they work. However, this information can be widely spread, hard to access and difficult to gain a working overview of, and the pace of changes and initiatives can seem almost dizzying. This book draws together a clear picture of the modern NHS, from funding and governance to reports, inquiries and overarching legislation. The book is clear and easy to understand and crucially includes full references to provide a one-stop point of access to the most detailed and up-to-date information available. This book is essential reading for workers in the NHS at all levels, including managers, administrators and clinical professionals. It is vital reading for managers and staff at commercial companies working with the NHS. It will also be of interest to campaigners, patient interest groups, researchers and journalists with an interest in the NHS. Specialty registrars and consultants can also find the information from the book, and much more, in The Doctor's Handbook Parts 1 & 2, by the same author. 'Rather than long narrative histories or complex explanations, the author signposts readers to sources of further information, making this book the quick guide so many of us need' - from the Foreword by Sir Ian Carruthers.